Determination of yeast microbiota in swine ear canal with and without ear secretion - Pulido-Villamarín, Adriana (2017)
Malassezia and Candida yeasts are considered part of the normal skin and mucosal microbiota in humans and other animals; however, there have been few studies on the pig’s ear canal microbiota. The aim of this study was to identify the yeast microbiota isolated from swabs of porcine ear canal. Primary isolation from 25 samples (16 and 9 pigs with and without brownish serous secretion) in Dixon and Sabouraud medium. Macroscopic and microscopic morphological features were described. Besides, biochemical, physiological and molecular tests were performed to identify the isolated yeasts. Fifty-five isolates were recovered and the molecular identification showed the presence of M. sympodialis (42.8%), M. slooffiae (28.6%), M. furfur (18.4%) and M. pachydermatis (8.2%).